Investigating the association between cataract and the risk of herpes zoster in a cohort study - Lai, Shih-Wei; Kuo, Yu-Hung; Liao, Kuan-Fu (Frontiers in Medicine, 2025)
ObjectivesThis cohort study aimed to elucidate whether individuals with cataract are at an increased risk of herpes zoster in Taiwan.MethodsA cohort of individuals with cataract, aged 20–84 years, was assembled from electronic health records of Taiwan National Health Insurance Program spanning a period of 8 years (2013–2020). Those individuals who had visited an ophthalmology clinic but did not have a cataract diagnosis were selected as the non-cataract group from the same database. The incidence rate of herpes zoster within the follow-up period was calculated between the two groups. The risk of herpes zoster was compared between the two groups using a Cox proportional hazards model, adjusting for potential confounders.ResultsThe cohort study included 1,299,685 individuals in the cataract group and 1,138,887 individuals in the non-cataract group. The mean age was 64 years older and about 43.9% of study subjects were male in the cataract group. The mean age was 63.6 years older and about 47.1% of study subjects were male in the non-cataract group. The incidence rate of herpes zoster was 10.84 per 1,000 person-years in the cataract group and 8.64 per 1,000 person-years in the non-cataract group (incidence rate ratio = 1.25, 95% CI = 1.24–1.27, P < 0.001). After adjusting for potential confounders, the hazard ratio was 1.22 for herpes zoster in individuals with cataract when compared with those without cataract (95% CI = 1.21–1.23, P < 0.001).ConclusionOur cohort study reveals that individuals with cataract are at an increased risk of developing herpes zoster. Our findings highlight the importance of considering the increased susceptibility to herpes zoster in individuals with cataract and the potential benefits of preventive measures such as herpes zoster vaccination.